The interaction effect of water deficit stress and seaweed extract on phytochemical characteristics and antioxidant activity of licorice (Glycyrrhiza glabra L.) - Fozi, Vahid; Esmaeili, Hassan; Alizadeh, Abouzar; Eghlima, Ghasem; Mirjalili, Mohammad Hossein (Frontiers in Plant Science, 2024)
With increasing drought stress due to climate change and water scarcity, the agricultural sector has sought innovative strategies to mitigate the detrimental effects on crop productivity. One approach that has received significant attention is the use of fertilizers and biostimulants as potential means of alleviating drought stress. In this study, five different irrigation levels including 100% (control), 80% (slight stress), 60% (mild stress), 40% (moderate stress), and 20% (severe stress) of field capacity (FC) and seaweed extract (SWE) at three concentrations (0, 5, and 10 g/L) were applied to the pots containing one-year-old licorice (Glycyrrhiza glabra L.) plants in a factorial completely randomized design experiment with three replications for eight weeks. The glycyrrhizic acid content increased with water stress intensity without the application of SWE until severe (20% FC) water stress treatment. The application of 10 g/L SWE under 100% FC led to a significant increase in the glycyrrhizic acid value (32.5±0.889 mg/g DW) compared with non-SWE application (30.0±1.040 mg/g DW). The maximum glabridin content (0.270±0.010 mg/g DW) was obtained under irrigation of 20% field capacity with 10 g/L SWE application. In addition, the activity of the all studied enzymes such as APX (ascorbate peroxidase), CAT (catalase), POD (peroxidase), and SOD (superoxide dismutase) were boosted by increasing the water stress levels. The use of SWE further enhanced the increase of some of these metabolites and enzymes, which, in turn, helped the plant to tolerate stress conditions through the scavenging of more ROS (Reactive oxygen species), wherein for this purpose, the SWE 10 g/L was more effective than other concentration. The plants efficiently eliminated ROS driven from drought stress by both nonenzymatic and enzymatic systems.